$14 million Ian R. Taylor Memorial Fund fosters talent development at SMU - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
Past and present staff of Vitol Asia have come together to make an endowed gift of $14 million to set up the Ian R. Taylor Memorial Fund (IRT-MF) at the Singapore Management University (SMU) in honour and memory of the late Mr Ian Roper Taylor (7 February 1956 – 8 June 2020). Mr Taylor was the former chief executive and chairman of the Vitol Group who transformed the small Dutch fuel merchant into the global commodities powerhouse that it is today.